2002
DOI: 10.1034/j.1600-079x.2002.02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nocturnal melatonin levels during acute myocardial infarction

Abstract: Acute myocardial infarction is accompanied by an increase in cellular oxidative stress in the pericardial coverings of the heart. Melatonin is a highly potent and efficient radical scavenger. Little research has been carried out concerning the relationship between this antioxidant and acute myocardial infarction in humans. In this work, serum levels of melatonin and parameters of oxidative stress, such as glutathione peroxidase and lipid peroxidation levels were examined in light/dark periods in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 28 publications
1
71
0
3
Order By: Relevance
“…26,49 Furthermore, previous studies have showed a decreased nocturnal serum melatonin in coronary heart disease and during acute myocardial infarction. 50,51 This approach raises new questions regarding the mechanism of endothelial dysfunction in preeclampsia and suggests that melatonin might be somehow involved.…”
Section: Discussionmentioning
confidence: 99%
“…26,49 Furthermore, previous studies have showed a decreased nocturnal serum melatonin in coronary heart disease and during acute myocardial infarction. 50,51 This approach raises new questions regarding the mechanism of endothelial dysfunction in preeclampsia and suggests that melatonin might be somehow involved.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы продукция МТ снижена у пожилых [6,9]; у больных с артери-альной гипертензией (М. Jonas, 2003) [4,9,14]; ИБС, в большей степени у больных стенокар-дией покоя (Р. Brugger, 1995) [4,7,9], ИМ [15]; с декомпенсацией хронической сердечной не-достаточности (ХСН) (L. Girotti, 2003) и др. [9].…”
Section: Shalenkova Ma Et Al шаленкова ма и дрunclassified
“…3), что не совсем согласуется с данными, полученными ранее в ра-ботах L. Girotti и соавт., А. Dominguez-Rodriguez и соавт. [15], Н.К. Малиновской и соавт.…”
Section: результаты и обсуждениеunclassified
“…In humans, melatonin production not only diminishes with age, but also lowers in many age-related diseases, including cardiovascular disease. 16,17 Coronary artery disease patients show a markedly decreased nighttime melatonin synthesis, 17 which may be assumed reason for absence of nocturnal dip in BP and high chances of myocardial infarction. 5 In addition, light/dark variations in the production of endogenous inflammatory markers in patients with CAD to some extent may be related to day/night fluctuations in circulating melatonin levels.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the mechanisms underlying this abnormal nighttime BP dipping pattern are not fully understood. 16 There is some evidence suggesting that a nondipping BP pattern may be related to advanced age, 21 sodium sensitivity, 22 postmenopausal status, 20 sleep apnea, and poor sleep quality. 21 Some studies state that melatonin supplementation at certain times during the night may function to increase endogenous melatonin level, potentially protecting against the melatonin downregulation associated with cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%